A new flightless species of the genus Trichiorhyssemus Clouët, 1901, from México (Coleoptera Aphodiidae: Psammodiinae) - Pittino, Riccardo (Instituto de Ecología, A.C., 2007)
The first known flightless species of Trichiorhyssemus Clouët, 1901 – T. hispidus sp. nov. – is hereby described and illustrated, from the State of Veracruz, Mexico. A key to Western Hemisphere species of the genus is also included.